ANALISIS EFEKTIVITAS PROGRAM BAZNAS DALAM MENINGKATKAN KESEJAHTERAAN MASYARAKAT MENURUT PERSPEKTIF EKONOMI ISLAM ” “(Studi kasus: Baznas Kabupaten Sijunjung )” - Edza Reva Delima; Zuwardi (Jurnal Ekonomi dan Bisnis, 2025)
The research conducted by the author aims to analyze the effectiveness of the Baznas program in enhancing community welfare from an Islamic economic perspective. This qualitative study utilizes a descriptive approach with data collection through interviews and documentation. The main issue identified in this research is that many residents of Sijunjung Regency are still unaware of these programs, which are designed to assist economically disadvantaged communities and improve overall community welfare.